2020
DOI: 10.3390/ma13112669
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Silicon Carbide Merged PiN Schottky Diodes with Electrical-Thermal Coupled Considerations

Abstract: A comparative study of surge current reliability of 1200 V/5 A 4H-SiC (silicon carbide) MPS (Merged PiN Schottky) diodes with different technologies is presented. The influences of device designs in terms of electrical and thermal aspects on the forward conduction performance and surge current capability were studied. Device forward characteristics were simulated and measured. Standard single-pulse surge current tests and thermal impedance measurements were carried to show their surge capability and thermal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Power semiconductors/modules inside inverters are the most crucial devices controlling the power conversion efficiency. In response to the urgent need for high-performance power conversion applications, the power semiconductor industry has recently seen rapid technological developments, such as insulated-gate bipolar transistors (IGBTs) [ 1 , 2 ], metal-oxide semiconductor field effect transistors (MOSFETs) [ 3 , 4 ], and even wide bandgap (WBG) silicon carbide (SiC) [ 5 , 6 ] and gallium nitride (GaN) power devices [ 7 ]. In contrast to IGBTs, MOSFETs comprise a number of advantageous features, such as a higher switching frequency and lower switching loss; accordingly, they have been used in a wide range of industrial applications, such as converters and inverters.…”
Section: Introductionmentioning
confidence: 99%
“…Power semiconductors/modules inside inverters are the most crucial devices controlling the power conversion efficiency. In response to the urgent need for high-performance power conversion applications, the power semiconductor industry has recently seen rapid technological developments, such as insulated-gate bipolar transistors (IGBTs) [ 1 , 2 ], metal-oxide semiconductor field effect transistors (MOSFETs) [ 3 , 4 ], and even wide bandgap (WBG) silicon carbide (SiC) [ 5 , 6 ] and gallium nitride (GaN) power devices [ 7 ]. In contrast to IGBTs, MOSFETs comprise a number of advantageous features, such as a higher switching frequency and lower switching loss; accordingly, they have been used in a wide range of industrial applications, such as converters and inverters.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have shown that a specially created design, which is described in detail in this article, allows well dissipation of the heat generated during the operation of the diode, and significantly increases the throughput of pulsed currents of diodes of this type. In Reference [ 1 ], it was demonstrated that high bipolar electrical conductivity causes overheating of the device, and the design of the device with a low thermal resistance can accelerate heat removal and limit the junction temperature during voltage surges. The authors cite in Reference [ 1 ] a description of the MPS diode design which can provide 60% higher pulse current density compared to other technologies.…”
mentioning
confidence: 99%
“…In Reference [ 1 ], it was demonstrated that high bipolar electrical conductivity causes overheating of the device, and the design of the device with a low thermal resistance can accelerate heat removal and limit the junction temperature during voltage surges. The authors cite in Reference [ 1 ] a description of the MPS diode design which can provide 60% higher pulse current density compared to other technologies.…”
mentioning
confidence: 99%
See 2 more Smart Citations